2003
DOI: 10.1063/1.1600737
|View full text |Cite
|
Sign up to set email alerts
|

Intense electron-beam ionization physics in air

Abstract: In this paper we study, experimentally and theoretically, the interactions of an intense electron beam with an initially-neutral background gas. The Naval Research Laboratory’s Gamble II generator [J. D. Shipman, Jr., IEEE Trans. Nucl. Sci. NS-18, 243 (1971)] was used to drive an annular 900 kV, 800 kA beam, whose effects on background air in the pressure range ∼0.01 to 10 Torr were studied. Experimental diagnostics included a sophisticated two-color interferometer for time-resolved measurements of the backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
5
0
3
Order By: Relevance
“…Propagation of the electron beam through fully ionized plasmas has been studied for several decades [3]. However, relatively few studies investigating the ionization dynamics of neutral materials have been reported [4][5][6][7][8].A high current density electron beam propagated through a neutral material can generate a large electrostatic field owing to the effect of charge nonneutrality. The large electrostatic field can directly ionize the neutral material, a process referred to as field ionization [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Propagation of the electron beam through fully ionized plasmas has been studied for several decades [3]. However, relatively few studies investigating the ionization dynamics of neutral materials have been reported [4][5][6][7][8].A high current density electron beam propagated through a neutral material can generate a large electrostatic field owing to the effect of charge nonneutrality. The large electrostatic field can directly ionize the neutral material, a process referred to as field ionization [9].…”
mentioning
confidence: 99%
“…Propagation of the electron beam through fully ionized plasmas has been studied for several decades [3]. However, relatively few studies investigating the ionization dynamics of neutral materials have been reported [4][5][6][7][8].…”
mentioning
confidence: 99%
“…The predecessor to this model [4] assumed an undissociated gas with singlyionized molecules, and used the localrfield approximation for the electron temperature, so that T,…”
Section: Model Detailsmentioning
confidence: 99%
“…A ring-diode experiment [4] used a twocolor interferometer to analyze the effects of a 140 ns annular electron beam, extending from 6.5 to 7.5 cm radius, transporting 800 kA at 900 kV through 1 to IO Ton air. In a second experiment, a paraxial diode generated a 30 U, 1.4 M v electron beam whose effects in air, argon and helium were studied.…”
Section: Experimental Comparisonmentioning
confidence: 99%
See 1 more Smart Citation